Inhibition of histone deacetylases in cancer therapy: lessons from leukaemia - Ceccacci, Elena (Br J Cancer, 2016)
Histone deacetylases (HDACs) are a key component of the epigenetic machinery regulating gene expression, and behave as oncogenes in several cancer types, spurring the development of HDAC inhibitors (HDACi) as anticancer drugs. This review discusses new results regarding the role of HDACs in cancer and the effect of HDACi on tumour cells, focusing on haematological malignancies, particularly acute myeloid leukaemia. Histone deacetylases may have opposite roles at different stages of tumour progression and in different tumour cell sub-populations (cancer stem cells), highlighting the importance of investigating these aspects for further improving the clinical use of HDACi in treating cancer.